Kommunikation zwischen dem Staat und den Bürgerinnen und Bürgern: linguistische Beiträge zu ihrer Optimierung - Hauck, Werner; Locher, Clemens; Lötscher, Andreas; Nussbaumer, Markus; Zangger, Alfred (My University, 2006)
The German Section of the Language Services in the Swiss Federal Chancellery strives to ensure the highest standards of communication between the state and its citizens. In this contribution, it will present four fields of activity that do not form part of its core business (drafting of legislation and translation) and which are consequently all the more reliant on theoretical and practical input from applied linguistics: (1) How can official letters (letters from government offices to individual citizens) be improved? (2) How does one accommodate general legal-political and media related requirements and the heterogeneous functions of political texts such as the "Explanatory Statements of the Federal Council", which are intended to explain the proposals being made to voters prior to a popular vote? (3) When giving names to government offices, how does one reconcile the need for matter-of-factness and transparency, and modernity and openness, while at the same time achieving linguistic accuracy and remaining true to Switzerland’s official languages? (4) What special requirements must official information intended for Internet publication satisfy and how can one optimise such texts?
Keywords: Regierungskommunikation; Verwaltung; Verständlichkeit; Institutionensprache; Fachsprache; Namen; Web-Texte